The factors influencing females' participation in University Bursaries Physical Education : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education in Special Education at Massey University - Girven, Wendi (Massey University, 1997)
The under-representation of females in University Bursaries Physical Education compared to their male counterparts was investigated to discover what factors influence females' participation. A variety of approaches including a postal survey, student and teacher perceptions questionnaires, focus group interviews and an informal discussion with physical educators were employed to examine the complexities and interpretations of Physical Education and sporting involvement as a physical phenomenon for females. An examination of the personal characteristics, needs, situational circumstances, the context and organisation of University Bursaries Physical Education revealed insights into the type of programmes that attract and cater for the interests of females. Results indicate that a 'gender-sensitive' and 'gender-fair' dimension was evident in those schools surveyed. Females believed that the curriculum was providing appropriate knowledge, skills, insights, attitudes and motivations that enabled them to develop their unique needs and abilities. It is anticipated that the information presented, the questions raised and the implications for future research and practice, will serve as catalysts for further discussion and research.
Keywords: New Zealand; Study and teaching (Secondary); Physical education and training; Sex differences in education